Proton Induced X-Ray Emission (PIXE) Analysis on Thick Samples at HUS 5SDH-2 Tandem Accelerator System - Khiem, Le Hong; Nghia, Nguyen The; Phong, Vi Ho; Loat, Bui Van (Communications in Physics, 2014)
The main purpose of this work is to establish a method of elemental analysis by Proton-Induced X-ray Emission (PIXE) technique on thick samples. Our study has been carried out at Hanoi University of Science (HUS) using a 5SDH-2 Tandem accelerator. The X-ray spectra were measured by a Si(Li) detector (FWHM = 139 eV at 5.9 keV) and analyzed off-line using GUPIX software. The validity of the proposed method has been checked through its application to NIST standard samples. The concentrations of the elements have been determined in the standard samples are in agreement with the certified values within the error limits. Our method is now used for the analysis of environmental samples at our laboratory